2015
DOI: 10.1364/ao.54.008444
|View full text |Cite
|
Sign up to set email alerts
|

Efficient generation of Hermite–Gauss and Ince–Gauss beams through kinoform phase elements

Abstract: We discuss the generation of Hermite-Gauss and Ince-Gauss beams employing phase elements whose transmittances coincide with the phase modulations of such beams. A scaled version of the desired field appears, distorted by marginal optical noise, at the element's Fourier domain. The motivation to perform this study is that, in the context of the proposed approach, the desired beams are generated with the maximum possible efficiency. A disadvantage of the method is the distortion of the desired beams by the influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Shaping of light fields in both amplitude and phase, requires in general a transfer function capable of modulating both, amplitude and phase. Since most SLMs allow only the direct control of the phase, several techniques have being proposed to indirectly modulate the amplitude [6,7,[33][34][35][36][37][38]. In this section we will briefly explain two of these techniques, phase-only and complex amplitude modulation.…”
Section: Experimental Generation and Multiplexing Of Modesmentioning
confidence: 99%
See 1 more Smart Citation
“…Shaping of light fields in both amplitude and phase, requires in general a transfer function capable of modulating both, amplitude and phase. Since most SLMs allow only the direct control of the phase, several techniques have being proposed to indirectly modulate the amplitude [6,7,[33][34][35][36][37][38]. In this section we will briefly explain two of these techniques, phase-only and complex amplitude modulation.…”
Section: Experimental Generation and Multiplexing Of Modesmentioning
confidence: 99%
“…In the above equation, mod[x] represents the modulus function that wraps the phase around 2π. A similar approach can be followed to generate HG nm beams [38]. Figure 2 shows the amplitude, phase and holograms encoded on the SLM for LG p 2(a) and HG nm 2(b) modes.…”
Section: Mode Generation and Multiplexing Using Phase Hologramsmentioning
confidence: 99%
“…Ren et al [ 12 ] reported the arbitrary generation of Ince–Gaussian beams using a digital micromirror device (DMD), which is an array of 1024 × 768 micromirrors with a switching frequency of 5.2 kHz. Aguirre et al [ 13 ] used kinoform phase elements for the generation of IG and HG beams. The generation of a helical Ince–Gaussian beam was reported by Bentley et al [ 14 ], who used a complex amplitude and phase mask encoded on a liquid crystal display.…”
Section: Introductionmentioning
confidence: 99%
“…However, the generation mechanism of the IG laser modes in SQS and PQS microchip lasers with a plane-parallel cavity is not clear. Usually, the generation mechanism of the high-order transverse mode can be catagorized as follows: phase modulation [11][12][13][14], gain control [15][16][17] and loss control [18,19]. The phase modulation requires the use of spatial light modulation devices such as the liquid crystal spatial light modulator [11,12], the kinoform phase elements [13] and the digital micromirror device [14].…”
Section: Introductionmentioning
confidence: 99%
“…Usually, the generation mechanism of the high-order transverse mode can be catagorized as follows: phase modulation [11][12][13][14], gain control [15][16][17] and loss control [18,19]. The phase modulation requires the use of spatial light modulation devices such as the liquid crystal spatial light modulator [11,12], the kinoform phase elements [13] and the digital micromirror device [14]. The IG mode can also be obtained in the solid-state laser with a plano-spherical resonator by off-axis pumping, which is a method of gain control [15,16]; however, this method does not work for microchip lasers with a plane-parallel cavity, because the symmetry of the plane-parallel cavity is not broken under the off-axis pumping.…”
Section: Introductionmentioning
confidence: 99%